Estimated neuronal populations and volumes of the hippocampus and its subfields in schizophrenia. - Walker, M; Highley, JR; Esiri, M; McDonald, B; Roberts, H; Evans, S; Crow, T (2002)
OBJECTIVE: It has been suggested that the primary focus of the pathological process in schizophrenia is on the limbic system, and there have been several postmortem reports of changes in the histological structure or volume of the hippocampus, as well as a larger number of MRI reports of volume reductions. There are conflicting findings, however, with both techniques. METHOD: The authors conducted a study of the gross and subfield structure and cellular composition of the hippocampus in postmortem brains from 30 patients with DSM-IV-diagnosed schizophrenia (13 women, 17 men) and 29 comparison subjects with no psychopathology (14 women, 15 men). Stereological sampling procedures were applied to 25-microm-thick coronal paraffin sections taken at 5-mm intervals throughout the formalin-fixed hippocampus. Subfields were defined as the dentate fascia, the hilus (CA4), an amalgamation of the CA2 and CA3 subfields, the CA1 subfield, and the subiculum. Volumes, cell densities, and cell numbers of the subfields were assessed microscopically, and the volume of the hippocampus was estimated from both photographs and histological slides of the coronal slices. RESULTS: As assessed from histologically stained slides, the volumes of the hippocampus and its subfields did not differ between patients and comparison subjects. Left-sided reduction in hippocampal volumes estimated from photographs, which may have included parahippocampal tissue, was not confirmed on histological examination. No significant differences were observed between patients and comparison subjects in the cellular composition of the hippocampus. CONCLUSIONS: These findings do not support a primary alteration of the hippocampus in schizophrenia.